Current Uses of Poly(lactic-co-glycolic acid) in the Dental Field: A Comprehensive Review. (9th March 2015) - Virlan, Maria Justina Roxana; Miricescu, Daniela; Totan, Alexandra; Greabu, Maria; Tanase, Cristiana; Sabliov, Cristina M.; Caruntu, Constantin; Calenic, Bogdan
Abstract : Poly(lactic-co-glycolic acid) or PLGA is a biodegradable polymer used in a wide range of medical applications. Specifically PLGA materials are also developed for the dental field in the form of scaffolds, films, membranes, microparticles, or nanoparticles. PLGA membranes have been studied with promising results, either alone or combined with other materials in bone healing procedures. PLGA scaffolds have been used to regenerate damaged tissues together with stem cell-based therapy. There is solid evidence that the development of PLGA microparticles and nanoparticles may be beneficial to a wide range of dental fields such as endodontic therapy, dental caries, dental surgery, dental implants, or periodontology. The aim of the current paper was to review the recent advances in PLGA materials and their potential uses in the dental field.